(untitled) (IASH Indian Journal of Arid Horticulture, 2024)
A field experiment was conducted during 2023-24 to evaluate the impact of organic and inorganic nutrients on the physico-chemical attributes of fig cv. Dinkar. The highest fruit size, including length (5.31 cm), width (5.42 cm), fresh fruit weight (44.38 g), dry fruit weight (21.48 g), fruit volume (45.70 cc), and specific gravity (0.970), were observed in plants applied with 75% NPK + 25% Poultry manure. Additionally, the highest values for TSS (18.86° Brix), reducing sugars (17.60%), non-reducing sugars (1.29%), total sugar (18.90%), and TSS/Acid ratio (93.21) were also recorded with 75% NPK + 25% Poultry manure. The lowest acidity (0.24%) was found in plants treated with 75% NPK + 25% Poultry manure, while the highest acidity (0.24%) was noted in those treated with 75% NPK + 25% Vermicompost. The highest ascorbic acid content (13.30 mg/100g pulp) was also observed in the 75% NPK + 25% Poultry manure treatment.